2002
DOI: 10.1046/j.1365-3024.2002.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii infection can regulate the expression of tumour necorsis factor‐α receptors on human cell in vitro

Abstract: The in vitro regulation of tumour necrosis factor (TNF)-alpha receptors during Toxoplasma gondii infection of human MRC5 fibroblasts and human myelomonocytic THP-1 cells was investigated. Cells were infected with the virulent RH of T. gondii. TNFR membrane receptors were analysed by flow cytometry with biotinylated TNF-alpha. Shedding of the soluble form of TNFR1 and TNFR2 in cell culture supernatants was measured by enzyme-linked immunosorbent assay, and expression of mRNA production of TNFR1 and TNFR2 was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 49 publications
0
20
1
Order By: Relevance
“…This study showed a maximal expression of TNF-R2 after infection at 4 h in both iDC and monocytes, which correlates well with the results from Belloni et al (18), who demonstrated a TNF-R2 up-regulation in Toxoplasma-infected THP-1 cells, also 3-4 h after infection with Toxoplasma. This is in contrast to another report that showed no increased expression of TNF-R2 after infection with Toxoplasma (29). Both of these studies used THP-1 cells in contrast to the iDC used in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…This study showed a maximal expression of TNF-R2 after infection at 4 h in both iDC and monocytes, which correlates well with the results from Belloni et al (18), who demonstrated a TNF-R2 up-regulation in Toxoplasma-infected THP-1 cells, also 3-4 h after infection with Toxoplasma. This is in contrast to another report that showed no increased expression of TNF-R2 after infection with Toxoplasma (29). Both of these studies used THP-1 cells in contrast to the iDC used in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study reported a capability of T. gondii to regulate expression of TNFRs in vitro (Derouich-Guergour et al, 2002), as shown by an enhanced release of soluble TNFR1 from infected cells. The resistance of T.-gondii-infected fibroblasts to apoptosis induced by TNFα raises the possibility of a downregulation of TNFR1 or TNFR2 during infection.…”
Section: Discussionmentioning
confidence: 97%
“…TRAPS presents clinically with self-limited inflammatory episodes (27). Therefore, in TRAPS patients, a proinflammatory event triggered by an environmental factor (such as infection [28,29], cancer [30,31], and drug toxicity [32]) that can up-regulate TNFRI expression will have an overall proinflammatory and antiapoptotic effect, because in the case of the T50K variant, which is capable of sustaining inappropriate NF-B activation, this will result in persistent production of proinflammatory mediators including TNF itself. A similar proinflammatory outcome has been shown in a mouse model of TRAPS (33).…”
Section: Discussionmentioning
confidence: 99%